Matéi Vișniec: cosmologias, ritos, espetáculos e performances - Galante, Camylla (2020)
Contemporary Matéi Vișniec‘s (1956 – ) dramaturgical production is composed by plays that transit through different themes: wars, ethnic conflicts, the role of the theater in the world, migrations, life of man in society. In each of his plays, Vișniec proposes reflections on several aspects of humanity, using the aesthetic of the absurd and of intrinsic characteristics of the hodiern theatrical productions for his composition, which, in their turn, are multiple and fragmented just like the contemporary man. Considering the aspects of this playwright‘s works, this thesis focus on analyzing his dramaturgical texts under different perspectives: as contemporary dramaturgical production, as object of anthropological analysis, as an allegory of the real world, and as a theatrical spectacle, in order to build a cosmology of the author. The research, of qualitative and biographical character, starts from the intra-textual comparative analysis – among some of the author‘s plays – and inter-textual, for also comprehending the study of spectacles based on Vișniec‘s dramaturgy. For such analysis, The body of a woman as a battlefield in the Bosnian War (1997/2012), On the sensation of elasticity when walking upon corpses (2009/2012), The word progress on my mother‘s lips doesn‘t ring true (2005/2012), Migraaants or There‘s too many people on this damn boat (2017), Decomposed theater or The human trashcan (1994/2012), Beware of old ladies cankered with loneliness (2003/2013), Old clown wanted (1993/2012), and Love letters to a Chinese princess (2012/2016) were the starting point plays. Among the spectacles, The body of a woman as a battlefield in the Bosnian War, directed by Fermando Philbert and with Ester Jablonski and Fernanda Nobre in the cast, is also listed in this thesis, as well as Goodbye, dead clowns, an interpretation of Old clown wanted, set by the Academia dos Palhaços (Academy of the clowns) company, directed by José Roberto Jardim; The word progress on my mother‘s lips doesn‘t ring true, set by the Temporall Companhia Cênica (Temporall Scenic Company) and directed by Reginaldo Nascimento; and Espelho para cegos (Mirror for blinds), in two versions, directed by Márcio Meirelles of Vila Velha Theater. The authors that support the theories on this thesis are divided in three aspects: regarding the contemporary theater, the basis is the propositions by Jean-Pierre Ryngaert (2013) and Jean-Pierre Sarrazac (2012); in the anthropological analysis of the theater, Stanley Tambiah (2018, 1997), Victor Turner (2015, 2008, 2005, 2013) and Richard Schechner (2011, 2006, 2012, 2013); as to the construction of the images, the propositions the thesis is based on are the ones by Octávio Paz (1982).